Local Hopf Birurcation and Stability of Limit Cycle in a Delayed Kaldor-Kalecki Model - Kaddar, A.; Talibi Alaoui, H. (Nonlinear Analysis: Modelling and Control, 2009)
We consider a delayed Kaldor-Kalecki business cycle model. We first consider the existence of local Hopf bifurcation, and we establish an explicit algorithm for determining the direction of the Hopf bifurcation and the stability or instability of the bifurcating branch of periodic solutions using the methods presented by O. Diekmann et al. in [1]. In the end, we conclude with an application.
Keywords: Kaldor-Kalecki business cycle; delayed differential equations; Hopf bifurcation; periodic solutions